(untitled) (Colombia Medica, 2015)
Introdution: The internal jugular vein locates anterior or anterolateral to the common carotid artery in two-thirds of the subjects studied by ultrasound when the head is in a rotated position. Aim: To identify variables associated with the anterior location of the internal jugular vein. Methods: Ultrasound examinations were performed with the patients in the supine position, with the head rotated to the opposite side. The proximal third of the neck was visualized transversely with a 7.5-mHz transducer. The relationship between the vessels was described in accordance with the proportion of the artery overlapped by the vein. Univariate comparisons and a multivariate analysis of potential variables that may affect the anatomic relationships were performed. Results: Seventy-eight patients were included, 44 of whom were men. The patients’ ages ranged from 17 to 90 years (median 64.0, interquartile range 41-73). The right and left sides were studied 75 and 73 times, respectively. The vein was located lateral to the artery in 24.3% (95%CI= 17.4-32.2) of the studies, anterolateral in 33.8% (95%CI= 26.2-41.4) and anterior in 41.9% (95%CI= 33.9-49.8). The multivariate analysis identified age group (OR= 3.7, 95% CI 2.1-6.4) and, less significantly, the left side (OR= 1.7, 95%CI= 0.8-3.5) and male gender (OR= 1.2, 95%CI= 0.6-2.7) as variables associated with the anterior position of the vein. Conclusión: The anterior position of the internal jugular vein relative to the common carotid artery increases gradually with age. Additionally, left-sided localization and male sex further increased the probability of an anterior position.